PENGARUH KUALITAS PRODUK DAN SEGMENTASI PASAR TERHADAP TINGKAT PENJUALAN PADA UD. NGREMBOKO KENCONO PS - Arri Syadah (CV SWA ANUGERAH, 2023)
Marketing is a series of processes ranging from planning to implementation, from promotion to distribution of goods or services in order to achieve the company's goal, namely the sale and purchase contract so as to generate profit or profit. Companies that have a good marketing concept will never escape the existence of consumer behavior that affects their sales level. The level of sales in the company is influenced by several factors to attract customers. For distributor companies or poultryshops, increasing sales has an important meaning to study. By knowing the level of sales, companies can examine and then determine what factors to strategies that can affect the level of sales. Based on these background, the following problems can be formulated: 1) How does the product quality variable partially and significantly affect the sales level at UD. Ngremboko Kencono PS; 2) How does market segmentation partially and significantly affect the sales level at UD. Ngremboko Kencono PS; 3) How does the effect of product quality and market segmentation simultaneously and significantly on the level of sales at UD. Ngremboko Kencono PS. By taking a sample, namely UD regular customers. Ngremboko Kencono as many as 50 people using correlation and regression analysis techniques. The results of the analysis can be concluded: 1) Product quality has a partial and significant effect on the level of sales at UD. Ngremboko Kencono PS; 2) Market segmentation partially and significantly affects the sales level at UD. Ngremboko Kencono PS; 3) Product quality and market segmentation simultaneously and significantly affect the sales level at UD. Ngremboko Kencono PS.